Anharmonic phonon coupling and decay of optical phonons in polycrystalline CdSe thin films. Issue 16 (15th August 2022) - Iqbal, Muhammad Faisal; Ullah, Kaleem; Yaqoob, Manzar Mushaf; Khan, Abbas Ahmad; Farid, Sumbal; Zhu, Peng; Wang, Deliang
Abstract: The lifetime of longitudinal optical (LO) phonon is a key parameter that significantly affects the performance of semiconductor optoelectronic devices. Herein, in situ temperature-dependent resonance Raman scattering experiment has been performed to study the phonon anharmonicity in sputter-deposited CdSe thin films. Strong multiphonon scattering processes involving 1LO + TO, 2LO-TO, 2LO + TO, 2LO+ E 2 low and TO- E 2 low are well resolved and allow us to investigate the anharmonic decay of 1LO, 2LO, and 1LO + TO phonon modes. Fundamental 1LO and its overtone 2LO phonon modes asymmetrically decay into a pair of transverse optical (TO) and transverse acoustical (TA) phonon at the 'A' point of the Brillouin zone along Γ−A direction. With increasing temperature, enhanced anharmonic phonon coupling and phonon decay led to an almost linear decrease in the wavenumber of both modes and a nearly linear increase in their full-width half maxima. The composite 1LO + TO mode exhibited a ∼ 30% faster decay rate compared to the decay rate of the fundamental 1LO phonon mode.